Integrating conventional system views with function-behaviour-state modelling - van Beek, Thom J.; Tomiyama, Tetsuo (Cranfield University Press, 2009)
The main contribution of this paper lies in the observations done in industry resulting in an approach of integrating the Function-Behaviour-State (FBS) model with user workflow and interface models to create complex system overview. On one side of the spectrum it focuses on modelling the usage of the system, while on the other side it considers the modelling and managing of interfaces. The choice for both these views is based on an industrial experience with the clinical Magnetic Resonance (MR) imaging system to manage design complexity. The paper gives a real example of the approach.
Organised by: Cranfield University
Keywords: Design complexity; function model; overview